Membentuk Generasi Unggul Melalui Strategi Manajemen Kurikulum di Era Digital - Muhammad Adzikra Irsy; Nadia Putri Nasution; Yesi Novita Sari; Merika Setiawati; Nikmah Hayati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research aims to analyze strategies for developing excellent generations through curriculum management in the digital era. The rapid advancement of technology and the dynamics of global competition necessitate educational institutions to adapt their curriculum management strategies to meet the demands of the digital era while fostering the development of an excellent generation. This qualitative descriptive study employed literature review and field observation methods at several educational institutions. The results indicate that effective curriculum management in the digital era requires integration of digital literacy, critical thinking, adaptive learning approaches, and strengthening character education. Implementation of curriculum management strategies focused on excellence includes: (1) curriculum design that balances academic, technological, and character competencies; (2) integration of digital platforms in learning processes; (3) enhancement of educators' digital competencies; and (4) participatory assessment methods. This research concludes that developing an excellent generation in the digital era requires comprehensive curriculum management strategies that incorporate technological advances while emphasizing character development and critical thinking skills.